ASSESMENT OF THE EFFECTIVENESS OF PHYSICAL ACTIVITY IN PELVIC ORGAN PROLAPSE (Conferencea, 2024)
Pelvic organ prolapses (POP) is a syndrome of prolapse of the pelvic floor and pelvic organs in isolation or in combination, which has an extremely negative impact on the quality o f life of patients. According to world data, from 2.9 to 53% o f women note some form of POP. Up to 47% o f patients with pelvic organ prolapse are women of working age. According to the Women, s Health Initiative Study, among 16 616 perimenopause women, the incidence of uterine prolapse was 14.2%, cystocele - 34.3%, rectocele - 18.6%. In most cases, POP is almost asymptomatic, which indicates its greater prevalence in the population.